Prospective Estimation of the Prevalence of Thromboembolism in Dogs With Inflammatory Protein‐Losing Enteropathy - Nene Oishi; Hiroshi Ohta; Masahiro Tamura; Kiwamu Hanazono; Kenjiro Miyoshi; Nozomu Yokoyama; Genya Shinbo (Journal of Veterinary Internal Medicine)
ABSTRACT Background Inflammatory protein‐losing enteropathy (iPLE) is thought to be associated with a hypercoagulable state and may predispose dogs to thromboembolism (TE). However, little information is available regarding the prevalence of TE in dogs with iPLE. Objectives Estimate the prevalence of TE in dogs with iPLE and collect clinical and clinicopathologic data from dogs with iPLE with and without TE. Animals Twenty‐two client‐owned dogs with iPLE. Methods Prospective, descriptive study. Dogs definitively diagnosed with iPLE based on standard diagnostic criteria and histopathology were recruited between January 2019 and February 2024. At the time of gastrointestinal endoscopic examination, dogs with iPLE underwent thoracic and abdominal computed tomography angiography to detect TE. Clinical (e.g., clinical severity, use of corticosteroids) and clinicopathologic (e.g., albumin concentration, coagulation parameters) data were collected from dogs with iPLE with and without TE. Results Thromboembolism was found in 3/22 dogs (13.6%, 95% confidence interval: 2.9–34.9) with iPLE. The three dogs with iPLE and TE had thrombi in the left external iliac artery, pulmonary artery of the right caudal lobe, and main portal vein, respectively. The dogs with thrombi in the left external iliac artery or pulmonary artery did not show any clinical signs associated with TE, whereas the dog with portal vein thrombosis had transudative peritoneal effusion. Conclusion and Clinical Importance We estimated the prevalence of TE in dogs with iPLE. In dogs with iPLE, TE could be underestimated because some affected dogs have subclinical TE.